In vitro fermentation characteristics and prebiotic activity of herbal polysaccharides: a review - Lai, Yong; Wang, Yu; Liu, Chang; Lou, Guanhua; Feng, Jianan; Li, Ying (Frontiers in Nutrition, 2025)
Herbal polysaccharides (HPs), as a category of macromolecular compounds, exhibits unique prebiotic benefits, including antioxidant and immunomodulatory effects, and regulatory effects on the gut microbiota. Particularly, the gut microbiota, often referred to as the ‘forgotten organ’ and the ‘second human genome’, plays a pivotal role in human health. In vitro fermentation techniques, including simulated gastrointestinal digestion and fermentation models, have emerged as effective tools for studying the gut microbiota and its relation to diseases. In vitro fermented polysaccharides can mimic the intestinal environment in vivo, which is crucial for understanding the mechanisms of polysaccharide metabolism, clarifying their metabolic pathways, and elucidating their prebiotic activity. By integrating high-impact research from the past 5 years, this review examines the structural changes of HPs during in vitro fermentation, their microbial metabolic mechanisms, and their prebiotic activity, addressing a current gap by integrating the ‘structure-microbe-function’ relationship within this field. The findings provide a theoretical basis for the effective utilization of traditional herbs, and offer insights for the development of novel functional products. Future studies should combine dynamic fermentation models with stratified clinical trials to accelerate the translational application of herbal polysaccharides.